Advances in the engineering of polysaccharide materials : by phosphorylase-catalyzed enzymatic chain-elongation - Kadokawa, Jun-ichi; Kaneko, Yoshiro (Pan Stanford Publishing ; Taylor & Francis [distributor], 2013)
Polysaccharides and their related compounds are attracting much attention due to their potential as new functional materials in many research fields such as medicine, pharmaceutics, foods, and cosmetics. Therefore, precision synthesis of new polysaccharides with well-defined structure is increasingly important. For this purpose, enzymatic method is a very powerful tool because the reaction proceeds in a manner that is highly stereo- and region-controlled. This book focuses on advances in the practical synthesis of polysaccharides by phosphorylase-catalyzed chain-elongation from the perspective.